High blood pressure tends to increase carotid intima-media thickness in adult females - Imran, Yudhisman; Prawiroharjo, Pukovisa; Mawi, Martiem (Universa Medicina, 2016)
BackgroundAtherosclerosis is initiated by endothelial dysfunction, asÂ a result of increasing degradation of nitrit oxide by reactive oxygen species, thereby increasing oxydative stress. Dyslipidemia is one of the risk factors of endothelial dysfunction. The aim of this study was to evaluate the relationship of blood pressure and serum lipid level with carotid intima-media thickness (CIMT) in subjects aged between 55-65 years.MethodsA cross sectional study was carried out in 52 male and female subjects aged between 55-65 years. Age, gender, body mass index (BMI), blood pressure, lipid profile, and CIMT were assessed in all subjects. The independent t-test was used to to analyze the relationship between all variables and CIMT. The level of statistical significance was set at p<0.05ResultsMean age was 59.19 Â± 3.68 years, prevalence of thickened CIMT was 66.5%, and plaques were found in 9 subjects. There wwre no significant differences in age, BMI, systolic and diastolic blood pressure, and lipid profile between normal and thickened CIMT (p>0.05). However, there was a significant difference in gender between the two groups (p=0.011). In females, mean systolic and diastolic blood pressure were higher in the thickened CIMT group than in the normal CIMT group, but the difference was not significant (p>0.05). ConclusionsOur findings suggest that high blood pressure tends to increase CIMT in female adults. An increasing value of CIMT should be considered as a sign of cerebrovascular disease.